Cultivating Equitable Partnerships Through Cultural Synthesis - Eric Conrad; Meghan Shewmake; Courtney Shows; Jen Nickelson (The University of Alabama, 2022)
The Holt Health Fair is a community event with the goal of providing health screenings and information dissemination to the community of Holt, Alabama. The inception of this annual event was developed through the formation of a collaborative between The University of Alabama (UA) students within the Delta Xi Chapter of the Eta Sigma Gamma (ESG) National Health Education Honorary, and members of the Holt community. Through the maturation of this partnership, stakeholder capacity has increased through mutual support and empowerment. This evolution is the direct result of a partnership that strongly values community voice and input. The following is a student perspective illustrating pertinent community engagement principles and their application in the development of the Holt Health Fair and community partnership.